Association between antiulcer agents and Clostridioides difficile infection in patients receiving antibiotics: A retrospective cohort study using the diagnosis procedure combination database in Japan. (June 2022) - Ishida, Ryo; Seki, Tomotsugu; Kawakami, Koji
Structured abstract: Objectives: To evaluate baseline risk for hospital onset Clostridioides difficile infection (HO-CDI) and the association with the use of antiulcer agents among patients undergoing antibiotic therapy in Japan. Methods: We conducted a retrospective cohort study using Japanese Diagnosis Procedure Combination database. Between July 2018 and January 2019, patients aged ≥18 years were included if they started antibiotics within two days of hospital admission. We defined exposure as proton pump inhibitors or histamine 2 receptor antagonists starting from day 2 to day 4 and the primary outcome as HO-CDI within 30 days. We performed multivariable analyses with complete cases using the propensity score (inverse probability treatment weighting [IPTW]) and several sensitivity analyses. Results: In total, 87, 137 patients were included. The median age was 78 years; 52.0% were men, and 23.6% received antiulcer agents. Within 30 days of admission, HO-CDI were observed in 0.41% and 0.26% of the antiulcer agent and control groups, respectively. IPTW revealed a positive association between antiulcer agents and HO-CDI (adjusted odds ratio, 1.33; 95% confidence interval [CI]: 1.13, 1.56). In the IPTW method, the risk difference was smaller (0.09%, 95% CI: 0.04%, 0.15%). Conclusion: The use of antiulcer agents in patients with antibiotics was associated with HO-CDI in Japan. However, the baseline risk and the difference in HO-CDI event rates were small; thus, as per several clinical practice guidelines, it is important to monitor antiulcer agent use and discontinue unnecessary use. The baseline risk should be considered when clinically evaluating the association between antiulcer agents and HO-CDI. Highlights: Among the patients with antibiotics, 23.6% received antiulcer agents. A positive association between antiulcer drugs and HO-CDI was observed in Japan. Most of CDI events were observed in patients with intra-abdominal infections. Baseline risk should be considered when clinically evaluating the association.